Long way down - Alexanian, David; Boorman, Charley; Malkin, Russ.; McGregor, Ewan. (Australia : EMI, 2007)
Motorcycle journey through Western Europe and Africa, from John o'Groats to Cape Town.
Disc 1: Ep. 1, 2, 3 plus extras -- Disc 2: Ep. 4 ,5 , 6 plus extras.
Dual layer format ; aspect ratio 16:9.
Keywords: Documentary television programs; Motorcycle touring -- Africa; Motorcycle touring -- Europe; Travelogues (Motion pictures, television, etc.)